The Role of Digital Literacy in Online Teaching: The Lecturers’ Perspectives - Harisa Mardiana (Athena: Journal of Social, Culture and Society, 2024)
This research explores how educators view digital literacy in virtual instruction, examining the impact of both internal and external factors on digital skills. Through a combination of methods, information was obtained from surveys completed by 103 lecturers and from detailed interviews with 15 lecturers in Tangerang City. Results indicate that 76.7% of respondents feel external factors, such as institutional support and infrastructure, are primary drivers for successful digital integration. Additionally, 69.9% of lecturers reported that internal factors, including attitudes, beliefs, and intentions, directly impact their digital teaching effectiveness. Educators proficient in digital literacy supported interactive online environments, while those with limited skills faced challenges that impacted student engagement and comprehension. The findings highlight the significance of ongoing digital literacy education, backing from organizations, and establishment of policies to encourage effective digital incorporation. These results emphasize the key role of digital literacy in improving online teaching and provide guidance for institutions seeking to enhance teacher preparedness in digital education